ONOMASTICS AS A BRANCH OF LINGUISTICS - Farmanov Gayrat Khujakulovich (PEDAGOGS, 2024)
Abstract. This article examines, analyzes, and discusses the specifics of linguistics as a research object, the place of onomastics in Uzbek linguistics today, and its future prospects.